2020
DOI: 10.1002/ajmg.a.61621
|View full text |Cite
|
Sign up to set email alerts
|

Maternal SLE and brachytelephalangic chondrodysplasia punctata in a patient with unrelated de novo RAF1 and SIX2 variants

Abstract: Our improved tools to identify the aetiologies in patients with multiple abnormalities resulted in the finding that some patients have more than a single genetic condition and that some of the diagnoses made in the past are acquired rather than inherited. However, limited knowledge has been accumulated regarding the phenotypic outcome of the interaction between different genetic conditions identified in the same patients. We report a newborn girl with brachytelephalangic chondrodysplasia punctata (BCDP) as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…Its incidence varies widely, with significant regional and ethnic disparities. For instance, the prevalence among Afro-Caribbean individuals in the UK spans a wide range, from as low as 0.3 per 100,000 to as high as 517.5 per million people (1,2). Studies in Asia have shown contrasting incidence rates in different countries.…”
Section: Introductionmentioning
confidence: 99%
“…Its incidence varies widely, with significant regional and ethnic disparities. For instance, the prevalence among Afro-Caribbean individuals in the UK spans a wide range, from as low as 0.3 per 100,000 to as high as 517.5 per million people (1,2). Studies in Asia have shown contrasting incidence rates in different countries.…”
Section: Introductionmentioning
confidence: 99%